Comparative efficacy and safety of antibiotic prophylaxis for reducing recurrent urinary infection in children : a systematic review and network meta-analysis (2024)
ABSTRACT: Context: There is uncertainty about the efficacy of antimicrobial agents as prophylaxis to reduce recurrent urinary tract infections in children, particularly between different types of antibiotics. Objective: Determine the comparative efficacy and safety of antibiotic prophylaxis for reducing recurrence urinary tract infection (UTI) in children. Data Sources: MEDLINE, Embase, Cochrane Central Register of Controlled Trials, CINAHL, LILACS, and grey literature, until January 5, 2024. Study Selection: Randomized controlled trials (RCTs) comparing the efficacy of different antibiotic therapies to placebo, no treatment, or each other in children to prevent UTI. Data extraction: Two reviewers independently screened abstracts and full texts, extracted the data, and assessed the risk of bias. We performed pairwise and network meta-analysis using the random-effects model. Results: We included 16 studies (3231 children). In the pairwise meta-analysis, we found that antibiotic prophylaxis reduces the risk of recurrence at 6 months (RR 0.53 [95%CI 0.41–1.68]; I2=54%) and 12 months (RR 0.65 [95%CI 0.47–0.89]; I2=58%), when compared to no treatment. In a grouped NMA evaluating the intervention as 'pediatrician-selected antibiotic (PSA)’ and when ‘fixed antibiotic’(FA) by the study, we found that PSA was superior to FA (OR 0.53[95%CI 0.32– 0.87]) and to no-treatment (OR 0.33 [95%CI 0.22– 0.48]). PSA was also superior to FA showing less antimicrobial resistance. In a second NMA, we evaluated antibiotics for recurrence at 6 months separately, and we found that nitrofurantoin (OR 0.31[95%CI 0.19– 0.49]), followed by PSA (OR 0.33 [95%CI 0.22– 0.48]) and TMP-SMX (OR 0.61 [95%CI 0.44– 0.82]) were superior to control. Subgroup analyses suggest PSA effects are larger in children under 2 years with VUR. Limitations: There was limited evidence for kidney scars, asymptomatic bacteriuria, and antimicrobial resistance. Conclusion: The antibiotic prophylaxis in children with UTI seems to reduce the risk of recurrent events at 6 and 12 months. This effect is probably higher in those under 2 years of age, identification of VUR and under 2 years of age with VUR.